The Situation of Student Dropout in Lower Secondary School Students in Had Pang cluster, Pak Ou District, Luang Prabang Province - LIAMAHER, yearher; Phaignavong, Somchay; Silivanh, Sommay; Sirirath, Khamphy; Keopaseuth, Dalyvone; Oudomsit, Houmpheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aimed to: 1) examine the level of opinions toward factors influencing school dropout among secondary school students in the Hat Pang cluster, Pak Ou District, Luang Prabang Province; and 2) identify the factors affecting school dropout among secondary school students in the Hat Pang cluster, Pak Ou District, Luang Prabang Province. This study employed a survey research design. The sample consisted of 75 former secondary school students in the Hat Pang cluster, Pak Ou District, Luang Prabang Province, who had already dropped out of school. A questionnaire was used to collect data, and the data were analyzed using the mean, standard deviation, and multiple regression analysis. The research findings revealed that: 1) The overall level of secondary school students’ opinions toward the factors contributing to school dropout across five aspects educational context, personal factors, family factors, economic factors, and social factors was at a high level (3.90, S.D. = 0.30). 2) The factors affecting school dropout among secondary school students in the Hat Pang cluster, Pak Ou District, Luang Prabang Province were family factors and educational context factors. These factors had predictive power and were able to explain 23.00% of the variance in the factors influencing school dropout in the Hat Pang cluster, Pak Ou District, Luang Prabang Province.